2020
DOI: 10.1029/2019ea000763
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Air‐Sea Interaction on the Eyewall Replacement Cycle of Typhoon Sinlaku (2008): Verification of Numerical Simulation

Abstract: To explore the effects of air‐sea interaction on the eyewall replacement cycle (ERC) of tropical cyclones (TCs), an ERC of Typhoon Sinlaku (2008) was reproduced using the high‐resolution coupled ocean‐atmosphere‐wave‐sediment transport (COAWST) model. The numerical simulations were evaluated with a wide range of observational datasets. Moreover, the importance of the ocean to ERC is discussed by comparing six sensitive experiments, that is, three uncoupled experiments with different time‐invariant sea surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…In contrast, UOC also undergoes an ERC but there is no significant weakening during the ERC and the moat between eyewalls is smaller than in C3D and C1D, which is similar to the intensification of Hurricane Irma during the ERC period (Fischer et al 2020) over a warmer ocean. Note that the limited contraction of the eyewall in the ERC due to SST cooling in our simulations is generally consistent with Yang et al (2019) and Li et al (2022). However, there are still differences between these studies.…”
Section: Eyewall Replacement Cyclesupporting
confidence: 92%
See 4 more Smart Citations
“…In contrast, UOC also undergoes an ERC but there is no significant weakening during the ERC and the moat between eyewalls is smaller than in C3D and C1D, which is similar to the intensification of Hurricane Irma during the ERC period (Fischer et al 2020) over a warmer ocean. Note that the limited contraction of the eyewall in the ERC due to SST cooling in our simulations is generally consistent with Yang et al (2019) and Li et al (2022). However, there are still differences between these studies.…”
Section: Eyewall Replacement Cyclesupporting
confidence: 92%
“…However, there are still differences between these studies. Yang et al (2019) found that the moat is larger in ocean-coupled experiments, but Li et al (2022) found that Trami's moat is not obvious in the coupled simulation. In this study, the moat of Trami is larger in C3D and the duration of the ERC period between coupled and uncoupled runs vary insignificantly, which is different from the simulation in Li et al (2022).…”
Section: Eyewall Replacement Cyclementioning
confidence: 99%
See 3 more Smart Citations